A Review of John Behr, The Mystery of Christ: Life in Death - Kaminis, Ioannis (Forum Theologicum Sardicense, 2025)
This paper reviews John Behr's "The Mystery of Christ: Life in Death." It discusses Behr's approach to theology, particularly his critique of modern historical criteria and his emphasis on a 'postmodern' understanding of faith centered on the transformative power of Christ. The review highlights Behr's engagement with contemporary theological trends and his call for a renewed dialogue between Orthodox theology and the challenges of modernity.